Nelson Rodrigues adaptador e adaptado: a vida como “deveria ser”, do conto à tela - Thomaz, Daniel de (2015)
This research deals with the study of the adaptation process languages that has as objective to analyze the transition from written text to audiovisual through intersemiotic translation (Jakobson). Specifically we focus on the tales from the ' A Vida Como Ela É..." by Nelson Rodrigues, originally published in a newspaper in the 50s and later adapted for television in 90. The choice of the theme is justified by the continued increase in volume literary productions adapted to different audiences and new electronic media. Its first foray analyzes the author's journey, trying to draw parallels between his fictional work and journalism in order to locate the series of tales as a watershed in the production of Brazilian serials and later dramaturgical work of the author. Thus, from constant negotiations between the two productions, we assign Nelson Rodrigues the function of "adapter", drawing upon, among several concepts, the poetic emulation as a method of his authorial insertion in the Brazilian imagination. In a second assault, we seek possible reasons to explain why television 90s was chosen media for adaptation and display of 40 short stories in serial formats aired weekly in the program Fantástico, Globo. From a political and economic analysis of so called decade of globalization, we understand that such choices would be associated to the concept of promise of a world organized, proposed by JOST (2007), this, as a whole, in televisual communication of stations open during this period. In this context, the television episode justifies its adaptive potential and a permeable work by intertextuality and dialogism according to the versions previously performed for radio, film and television. Opting for the theoretical and practical methodology, this research is mainly an analysis of original content (written) and adapted (television) trying to find conjunctions, disjunctions and transmutations in the transition from one form to another. This is accompanied by an interview with the serial adapter and bibliographic research in order to provide a thorough reflection on the potential of authors and works to adapt to new languages and media. For this, in our specific objectives, we proposed the creation of categories of analysis, or adaptability factors, namely the receptive creativity, variability of formats, thematic break and crack narrative.